Muslim Friendly Index Pusat Perbelanjaan di Surabaya - Gani, Redy Barlian; Suprayogi, Noven (Universitas Negeri Surabaya, 2023)
Shopping malls play a significant role as halal tourism destinations, necessitating their adherence to criteria that cater to Muslim tourists. To address this need, Crescent Rating has developed an indicator specifically for Muslim-friendly tourist destinations. Surabaya, Indonesia's second-largest city, boasts numerous shopping malls that hold potential as halal tourism sites. This research aims to gauge the Muslim-friendly index in Surabaya's shopping malls and compare it based on the malls' building area and the percentage of the Muslim population in their respective locations. The Muslim-friendly index relies on various indicators, including the faith-based service needs of Muslim travelers and a modified version of the Access, Communications, Environment, Services (ACES) model provided by Crescent Rating. For the sample is purposively selected shopping malls in Surabaya. Data was collected through surveys, observations, and the analysis of social media content pertaining to these malls. Descriptive statistical analysis and the Mann-Whitney statistical test were employed to analyze the gathered data. The research findings indicate that Surabaya's shopping malls possess a moderate Muslim-friendly index. Furthermore, there is no discernible variation in the Muslim-friendly index across the malls, whether based on their building area or the percentage of the Muslim population in their vicinity.